European markets in cocaine - Lewis, Roger (Contemporary crises, 1989)
An established market for illicit cocaine has existed in Europe for twenty years. There is considerable elasticity in demand. Over-production in Latin America has contributed to increased availability and consumption. Retail prices vary from country to country. Professional criminals have become heavily involved in the market since the 1970s. The effect of cocaine trafficking on criminal organization may prove to be more significant than any problematic drug use resulting from the traffic itself.